Response Surface Methodology for Development and Characterization of Extruded Snack Developed from Food-by-products - Raleng, Angam; Singh, Amarjit; Singh, Baljit; Attkan, Arun Kumar (International Journal of Bio-resource and Stress Management, 2016)
The aim of the present study was to optimize the extrusion process for pineapple-based snacks using response surface modelling approach. A blend of pineapple waste pulp powder (0–20%), broken rice (0–80%) and pigeon pea (0–20%) were extruded in a twin-screw extruder. The effects of feed moisture, barrel temperature, screw speed on product responses viz., specific mechanical energy (SME), bulk density (BD), water absorption index (WAI), water solubility index (WSI), hardness and expansion ratio (ER) was studied using response surface methodology. The formulation was extruded at different moisture content (14–18%), screw speed (400–550 rpm) and die temperature (120–180 °C). The extrudates developed under optimized conditions contains 5.27% of moisture wb, 4.96% of protein, 3.05% of fibre, 2.18% of ash and colour L-value of 66.18, a-value of 1.91, b-value of 16.71. Feed moisture had significant effect on all products responses, whereas pineapple pomace level and barrel temperature, both independent variables, had significant effect on SME, WSI and hardness of the product. Increase in feed moisture reduces SME and WSI and increases BD, WAI and hardness. Increase in pineapple pomace level decreases the BD, WAI and hardness of the snacks, whereas increase in barrel temperature decreases the SME, BD, WAI and hardness but increases the WSI. Optimized extrusion parameters for preparation of snacks were 17.16% moisture, 120° temperature and 6% pineapple pomace powder.